2020
DOI: 10.1080/22221751.2020.1763858
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the first detected human case of low pathogenic avian influenza A/H9N2 in sub-Saharan Africa, Senegal

Abstract: The H9N2 influenza virus has become one of the dominant subtypes of influenza virus circulating in poultry, wild birds, and can occasionally cross the mammalian species barrier. Here, we report the first human A/H9N2 in Sub-Saharan Africa. The patient was a child of 16 months' old living in the SouthWest of Senegal. He had no influenza vaccination history and no other disease history. He had symptoms of fever with an auxiliary temperature of 39.1°C. Respiratory symptoms were an intense cough, runny nose and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Additionally significant is the zoonotic potential of the H9N2 isolates from Nigeria as they harbor the mammalian adaptation markers I155T and Q226L (H3 numbering) in the HA gene, which promote preferential binding to human-like α2-6-linked sialic acid receptors [25]. These mutations have been reported in H9N2 found in other African countries [13,14,16]. Silent circulation of H9N2 with less than optimum biosecurity makes the virus more likely to be transmitted to other species akin to the observation by Meseko et al [26] where H5N1 was transmitted to domestic pigs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally significant is the zoonotic potential of the H9N2 isolates from Nigeria as they harbor the mammalian adaptation markers I155T and Q226L (H3 numbering) in the HA gene, which promote preferential binding to human-like α2-6-linked sialic acid receptors [25]. These mutations have been reported in H9N2 found in other African countries [13,14,16]. Silent circulation of H9N2 with less than optimum biosecurity makes the virus more likely to be transmitted to other species akin to the observation by Meseko et al [26] where H5N1 was transmitted to domestic pigs.…”
Section: Discussionmentioning
confidence: 92%
“…An increasing number of H9N2 infections in humans have been reported in the world [ 12 ]. In Africa, five human cases have been reported since 2015, four in Egypt and one in Senegal [ 16 ]. Together with its zoonotic potential, the circulation of this subtype with other avian influenza virus subtypes is of great concern considering the risk of the emergence of novel reassortant viruses with unpredictable biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, H9N2 IAVs are zoonotic viruses themselves and have also been reported in other mammalian species such as swine, dogs, horses, and mink. In humans, H9N2 IAV infections have presented with mild influenza-like symptoms such as respiratory symptoms, coughing, fever, nasal discharge, sore throat, and headache [48][49][50][51][52]. Only one fatality has been associated with H9N2 IAV infection in humans to date [53].…”
Section: H9n2 Avian Influenza Virusesmentioning
confidence: 99%
“…H9N2 can infect humans directly and cause respiratory diseases with varying degrees of severity. The first human case of H9N2 infection was reported in China in 1998, with several subsequent cases reported in China ( Peiris et al., 1999 ; Butt et al., 2005 ; Huang et al., 2015 ; Yuan et al., 2017 ; Pan et al., 2018 ; Guo et al., 2020 ), Pakistan ( Ali et al., 2019 ), India ( Potdar et al., 2019 ), Oman ( Almayahi et al., 2020 ), Bangladesh ( Shanmuganatham et al., 2013 ), Cambodia ( Um et al., 2021 ), Egypt ( Gomaa et al., 2020 ), and Senegal ( Jallow et al., 2020 ) in the following 20 years. Previous studies have revealed that H9N2 viruses can contribute internal genes to other subtypes of AIV.…”
Section: Introductionmentioning
confidence: 99%